Analysis of Physical and Mechanical Properties of Universal Composites under Different Types of Polishing before and after Acid Challenge - José Roberto Vergínio de Matos; Letícia Barbero Antunes; Isabela Araguê Catanoze; Isabela Saturnino de Souza; Paulo Henrique dos Santos; Aimée Maria Guiotti (Hindawi Limited, 2024)
This study aimed to evaluate in vitro the degree of surface smoothness provided by two different polishing techniques and the effect of acid challenge on the alteration of surface roughness (Ra), microhardness (Knoop), and color (ΔE00) of three nanoparticulate composites, simulating 1 year of exposure to hydrochloric acid (HCl). Eighty specimens for each composite were divided into four groups (n = 240), being control without polishing, control with wear, WPC (wear + polishing with Cosmedent Kit), and WPB (wear + BisCover LV liquid polish). Repeated measures ANOVA was applied for Ra and Knoop Microhardness. For the color (ΔE) three-way ANOVA was applied. In cases of statistically significant the Tukey posttest was applied (α = 0.05). Both types of polishing tested resulted in a surface smoothness below the critical value established by the studies (Ra ≥ 0.2 μm), even after immersion. The microhardness of all composite resins decreased after the challenges. The specimens immersed in HCl showed a lower microhardness (42.2 Kgf/mm2) when compared to the specimens immersed in artificial saliva (44.7 Kgf/mm2). Regarding the color change, the composites presented values compatible with clinical acceptability, with a statistically significant difference only between the control group and the other types of polishing for the Z350 XT resin (ΔE00 = 3.78). It was concluded that both mechanical and chemical polishing produced a satisfactory surface smoothness, even after immersions in artificial saliva and HCl. The microhardness of the composites was affected by the challenges and the composites tested were within clinical acceptability with regard to color change.